POTATO MINI-TUBER PRODUCTION THROUGH DIRECT TRANSPLANTING OF IN VITRO PLANTLETS IN GREEN OR SCREEN HOUSES – A REVIEW - Sharma, Ashwani K; Pandey, K K (Potato Journal, 2013)
The mini-tuber production technology involving direct transplanting of in vitro plantlets in green or screen houses is though commonly followed but still requires more research on the production and pre-treatment of the in vitro plantlets before planting as well as on subsequent management of the crop afterwards. Majority of the physiological and agronomical aspects like age of plantlets at planting, method and duration of hardening, growing media in green or screen houses, season, method of planting, plantlet density, use of plantlet (full or part), fertilizer doses, irrigation, inter-culture, crop duration as well as development of some special cultivation techniques like hilling etc. need to be investigated further for maximizing the number of mini-tubers per in vitro plantlet as well as for improving the size of mini-tubers while reducing the proportion of extremely small sized mini-tubers for successful multiplication in open fields.